Relationship between hepatitis B DNA Viral load in the liver and it\'s histology in patient with chronic hepatitis B - Tahmineh Biazar; Yousef Yahyapour; Mohammad Reza Hasanjani Roushan; Ramazan Rajabnia; Mahmoud Sadegi; Hasan; Mohammad Ranaei; Masomeh Bayani (Babol University of Medical Sciences, 2015)
Background: Serial measurement of  hepatitis B virus (HBV) DNA levels in the liver and its relation with liver damage and serum HBV DNA levels are guide to begin and/or end a treatment course. This study evaluated the relationship between liver hepatitis B DNA viral load with liver histology in patients with chronic hepatitis B (HBV). Methods:  Thirty patients with chronic anti-Hbe positive hepatitis B, with liver enzymes &ge 2 times of the upper limit of normal and positive HBV DNA of any amount were entered in the study. They underwent percutaneous liver biopsy. Liver and serum viral load were determined using real time polymerase chain reaction (RT-PCR) method. Liver function tests and liver histology for all cases were recorded. The amount of viral load in the liver and histological grading and staging were recorded. Data were collected and analyzed. Results: The mean age of the patients was 32.8±10 years and 24 (80%) patients were males. Ten (33.3%) patients had HBV viral load levels less than 20000 IU/mL. There was a significant correlation between liver viral load levels with staging or grading of liver damage. Conclusion: The results of the present study showed a strong correlation between liver viral load and liver damage in patients with chronic hepatitis B.